IMPLEMENTASI DAN ANALISIS PERFORMA JARINGAN DISKLESS SYSTEM STANDAR DENGAN DISKLESS SYSTEM CLUSTER - Ramadhani, Hairul (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
This research aims to achieve bothefficiency and effectiveness in managing a networkcomputer using Linux Ubuntu 12.04 with LinuxTerminal Server Project (LTSP) application, byusing a computer that does not come with a harddrive (diskless). And also to improve theeffectiveness of the use of LTSP on implementationwith many LTSP client with LTSP Cluster and totest the application of wireless bridge to thenetwork medium that used for LTSP. the benefits tobe achieved in this research is to improve the LTSPserver performance effectiveness at a time whenmany thin client applied and at the time when LTSPimplemented in a places that are difficult to reachwith the LAN network. With LTSP, it is expected topush the cost of the equipment as well as long-terminvestments that are charged to one of theestablishments or places that require the use ofoptimization of device to always adjust and keep upwith the development of technology that wasadopted such as the operating system or software.This problems occurs due to the use of architecturethat generally requires compatibility of all devicesthat used. The solution of the problem is to apply athin-client architecture. So not all the computersmust be upgraded or replaced. Only server-sidedevice is adjusted in order to adopt the technologyand operating system software. In terms of fulfillingthe compatibility that desired.